Calidad bacteriológica y desechos sólidos en cinco ambientes costeros de Costa Rica - García Cortés, Vera (2006)
Anthropogenic waste and water bacteriological quality were surveyed twice a year in 2000 and in 2002 at five coastal marine environments in Costa Rica, one in the Caribbean (Moín Bay) and four in the Pacific (Culebra Bay, Gulf of Nicoya, Puntarenas Estuary, Golfito Bay). The most probable number (MPN)/100 mL of coliform bacteria was calculated after incubation series of five test tubes. We collected a total of 14 coastal and two river water samples in the Caribbean, and 32 coastal, nine estuarine and one tap water samples in the Pacific, plus 25 samples investigated for Escherichia coli in 2002. We used the means of <200 MPN/100 mL for total coliforms and <100 MPN/100 mL for faecal coliforms, as bacteriological criteria for safe swimming. All following data are geometric means. Golfito Bay was the most contaminated zone, with total coliforms of 51 353 MPN/100 mL in May, 6 243 MPN/100 mL in November 2000; and 5 485 MPN/100 mL in February and 14 102 MPN/100 mL in November 2002. For faecal coliforms, values were 51 353 MPN/100 mL and 1 015 MPN/100 mL in May and November 2000, respectively. In 2002 the values were 923 MPN/100 mL and 7 127 MPN/100 mL in February and November, respectively. The least polluted region was Culebra Bay, with total coliforms of >2 MPN/100 mL in June 2000 and 17 MPN/100 mL in May 2002, and faecal coliforms <2 MPN/100 mL in June 2000 and 4 MPN/100 mL in May 2002. Plastic materials were the most abundant item stranded in all beaches, which in more than 80% of the occasions were between “moderately dirty” to “very dirty”. Rev. Biol. Trop. 54 (Suppl. 1): 35-48. Epub 2006 Sept. 30.